Pengaruh Roadcel-50 Terhadap Pengujian Marshall dengan Suhu Tinggi pada Campuran Beton Aspal. - Perpustakaan UGM, i-lib ([Yogyakarta] : Fakultas Kehutanan UGM, 1999)
ABSTRACT Roadcel-50 is one of the type of additive to improve properties of hottnix asphaltic concrete. It increases a softening point and reduces a penetration of bitumen, so that a hotmix becomes more stiffness, more stable, and reduces a surface cracking due to high temperature. Samples of asphaltic concrete are made with Roadcel-50 as an additive. The content of Roadcel-50 in the research is 0%